2020
DOI: 10.1016/j.euromechflu.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and fluid flow-induced wall shear stress in bone scaffolds with TPMS and lattice architectures: A CFD analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(63 citation statements)
references
References 49 publications
4
59
0
Order By: Relevance
“…2), the parameters of which are described in Table. The table presents the physical parameters of the simulated scaffolds, according to which their average pore size is in the range from 3 to 7 mm, while their masses are comparable, the average mass is 8.213 ± 0.13 g. Obviously, the geometric shape and pore sizes affect the porosity of the entire scaffold structure, and according to the calculations, the average porosity value is 0.705 ± 0.06. The measurement of the values of the volume fraction of voids for all types of scaffold structures varied from 64 to 76%, which is consistent with the data presented in experimental works [39][40][41][42]. Figure 3 shows the results of numerical simulation of the rate of diffusion flow of nutrients based on glucose in the porous structure of different types of scaffolds.…”
Section: Results Of Internal Flow Modelingsupporting
confidence: 87%
See 1 more Smart Citation
“…2), the parameters of which are described in Table. The table presents the physical parameters of the simulated scaffolds, according to which their average pore size is in the range from 3 to 7 mm, while their masses are comparable, the average mass is 8.213 ± 0.13 g. Obviously, the geometric shape and pore sizes affect the porosity of the entire scaffold structure, and according to the calculations, the average porosity value is 0.705 ± 0.06. The measurement of the values of the volume fraction of voids for all types of scaffold structures varied from 64 to 76%, which is consistent with the data presented in experimental works [39][40][41][42]. Figure 3 shows the results of numerical simulation of the rate of diffusion flow of nutrients based on glucose in the porous structure of different types of scaffolds.…”
Section: Results Of Internal Flow Modelingsupporting
confidence: 87%
“…3b) indicates that the pores do not significantly affect the rate of nutrient spread. Such behavior at similar parameters is confirmed in experimental works [42,[46][47][48] and possibly indicates the selection of the optimal scaffold rotation rate. At rotation rates of 24 rpm (Fig.…”
Section: Results Of Internal Flow Modelingsupporting
confidence: 66%
“…It could be seen in the results that the D surface had the highest specific surface (Guo et al, 2019). At the same time, many pieces of research indicated that the G surface had the highest permeability, which means adequate oxygen and nutrition delivery (Montazerian et al, 2017(Montazerian et al, , 2019Yang et al, 2018;Castro et al, 2019a;Ali et al, 2020). Therefore, the D and G surface might have the best bone growth, which needs to be verified by future biological experiments.…”
Section: Tpmsmentioning
confidence: 95%
“…They were regarded as effective tools for designing scaffolds with gradual and regular porous structures [11,12]. Recently, Ali et al [13] designed eight different bone scaffolds based on TPMS and proved these architectures have a significant impact on permeability. Li et al [14] successfully prepared the Ti6Al4V scaffold with TPMS of p-cell.…”
Section: Introduction mentioning
confidence: 99%